How to take into account vulnerability in aid allocation criteria and lack of human capital as well: improving the performance based allocation - Patrick Guillaumont; Sylviane Guillaumont Jeanneney; Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
This paper considers why and how the Performance Based Allocation (PBA) used in multilateral development banks and in particular at IDA, could be improved by taking the structural handicaps of eligible countries into account. The PBA relies on a debatable definition of performance. It does not meet the equity concern raised by the existence of structural handicaps to growth. It neglects the lessons of the aid effectiveness literature. Finally, it suffers from some opacity. We show how it is possible to increase the share of specific groups of countries, such as Sub-Sahara Africa or post-conflict states, in a transparent manner.
Keywords: F35; F33; O19; 330; PBA; Vulnérabilité; PMA; Capital Humain